2018
DOI: 10.1002/jcb.27698
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin protects hippocampal neurons from oxygen‐glucose deprivation–induced injury

Abstract: Daphnetin, a coumarin derivative extracted from Daphne odora var., was reported to possess a neuroprotective effect. Recently, it has been demonstrated that daphnetin attenuates ischemia/reperfusion (I/R) injury. However, the role of daphnetin in cerebral I/R injury and the potential mechanism have not been fully understood. The present study aimed to explore the regulatory roles of daphnetin on oxygen-glucose deprivation/reoxygenation (OGD/R)-induced cell injury in a model of hippocampal neurons. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…49,50 OGD results in ischemic neuronal damage through activation of autophagy, neuroinflammatory responses, and induction of apoptosis in the hippocampal neuron in vitro. 51 OGD-induced apoptotic cell death occurs by the inhibiting the PI3K/AKT and BDNF/TrkB pathways, 40,52 and the neuroprotective effects of both URB597 and VEGF-A may be dependent on the activities of these two pathways. We previously demonstrated that URB597 could improve chronic cerebral ischemia-induced neuronal degeneration and apoptosis via activating CB1R/ AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 OGD results in ischemic neuronal damage through activation of autophagy, neuroinflammatory responses, and induction of apoptosis in the hippocampal neuron in vitro. 51 OGD-induced apoptotic cell death occurs by the inhibiting the PI3K/AKT and BDNF/TrkB pathways, 40,52 and the neuroprotective effects of both URB597 and VEGF-A may be dependent on the activities of these two pathways. We previously demonstrated that URB597 could improve chronic cerebral ischemia-induced neuronal degeneration and apoptosis via activating CB1R/ AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, daphnetin positively upregulated Nrf2 while it inhibited the expression Keap1 in HG-stimulated MCs [135]. Zhi et al reported that daphnetin protected hippocampal neurons exposed to oxygen-glucose deprivation-induced injury against I/R via marked enhancement of the nuclear translocation of Nrf2 and HO-1 expression [136]. Moreover, Nrf2 knockdown blocked the protective effect of daphnetin on I/R in hippocampal neurons, confirming the critical role of Nrf2/HO-1 signaling activation in the neuroprotective effect of daphnetin [136].…”
Section: Urolithin Amentioning
confidence: 99%
“…Zhi et al reported that daphnetin protected hippocampal neurons exposed to oxygen-glucose deprivation-induced injury against I/R via marked enhancement of the nuclear translocation of Nrf2 and HO-1 expression [136]. Moreover, Nrf2 knockdown blocked the protective effect of daphnetin on I/R in hippocampal neurons, confirming the critical role of Nrf2/HO-1 signaling activation in the neuroprotective effect of daphnetin [136]. Lv and coworkers demonstrated that daphnetin effectively inhibited cytochrome c release and NLRP3 inflammasome activation through upregulation of the Nrf2 nuclear translocation along with Keap1 protein downregulation [137].…”
Section: Urolithin Amentioning
confidence: 99%
“…IACUC A1027). All animals were cared for in accordance with the recommendations of the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health (28).…”
Section: Fundingmentioning
confidence: 99%
“…Liu et al (26) reported that DAP has some protective effects on severe acute pancreatitis in a rat model by inhibiting the expression of inflammatory cytokines. Subsequently, DAP was found to prevent and treat numerous diseases, including cerebral ischaemia/reperfusion injury, rheumatoid arthritis, colitis and endotoxin-induced lung injury, due to its powerful anti-inflammatory activities (24,(27)(28)(29)(30)(31)(32). At present, DAP is an anti-inflammatory agent used in some inflammation-related diseases (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%